Positive Feedback Regulation between Transglutaminase 2 and Toll-Like Receptor 4 Signaling in Hepatic Stellate Cells Correlates with Liver Fibrosis Post Schistosoma japonicum Infection - Wen, Zhencheng; Ji, Xiaofang; Tang, Juanjuan; Lin, Guiying; Xiao, Linzhuo; Liang, Cuiying; Wang, Manni; Su, Fang; Ferrandon, Dominique; Li, Zi (Frontiers in Immunology, 2017)
Liver fibrosis induced by Schistosoma japonicum (Sj) infection is characterized by the accumulation of extracellular matrix (ECM). The activated and differentiated hepatic stellate cells (HSCs) are the predominant ECM-producing cell type in the liver. TLR4 pathway activation plays a key role in mice liver fibrosis models induced by alcohol, biliary ligation, and carbon tetrachloride 4. In this work, we found that TLR4 pathway activation correlated with the severity of liver fibrosis post Sj infection. The TLR4 receptor inhibitor TAK242 reduced the extent of liver fibrosis. The increased expression of TLR4, α-smooth muscle actin (α-SMA) and cytoglobin was observed in the HSCs of mouse liver after Sj infection. In response to stimulation with either lipopolysaccharide or Sj's soluble egg antigen (SEA), high levels of TLR4 and α-SMA were induced in HSCs and were inhibited by TAK242 treatment. In previous work, we had reported that a high level of transglutaminase 2 (TGM2) is crucial for liver fibrosis post Sj infection. Herein, we found that TLR4 signaling also controlled Tgm2 expression. Inhibition of TGM2 activity by cystamine (CTM) in Sj-infected mice or in HSCs induced with all-trans-retinoic acid (ATRA) stimulation led to a lowered activation of TLR4 signaling and a reduced α-SMA expression. These results were confirmed by down-regulating the Tgm2 gene by specific siRNA. These observations implied the presence of a positive feedback regulation between TGM2 and TLR4 signaling in HSCs that correlated with liver fibrosis post Sj infection. This novel connection between TGM2 and TLR4 pathway activation in liver fibrosis induced by Sj infection enhances our understanding of liver diseases.